Crash-involved THC-positive drivers in Norway have a high frequency of polysubstance use. (1st March 2023) - Gjerde, Hallvard; Bogstrand, Stig Tore; Jamt, Ragnhild Elén Gjulem; Vindenes, Vigdis
Abstract: Background: Tetrahydrocannabinol (THC) is the most frequently detected drug in blood samples from apprehended drug driving suspects in Norway. This investigation aimed to study the extent of polysubstance use among apprehended crash-involved drivers with THC concentrations above the legal limit and explore the importance of THC in polysubstance cases. Methods: We selected all drug driving cases where blood samples had been submitted for forensic toxicology testing after involvement in road traffic crashes during 2013–2020, except drivers who were fatally injured. Results: Twenty percent (n = 2133) of the 10, 520 apprehended crash-involved drivers had concentrations of THC in their blood above the legal limit of 1.3 ng/mL, and 84 % of those also had concentrations of alcohol or other drugs above the legal limits; 61 % for sedatives, 38 % for stimulants, 33 % for alcohol, and 10 % for opioids. The most frequent substance combination was cannabis together with sedatives and stimulants (22.9 %; n = 488). Polysubstance use was least common among drivers under 24 years. The proportion of drivers with THC > 5 ng/mL was highest if the blood sample was collected within 90 min after the crash, and when only THC was detected. There was a statistically significant inverse association between THC > 5 ng/mL and concentrations of alcohol or amphetamines at the highest sanction level. Conclusions: Most apprehended crash-involved THC-positive drivers also tested positive for other psychoactive substances. Drivers with high blood THC concentrations had less often high concentrations of other substances; cannabis might then have been a more important contributor to impairment. Highlights: 20 % of all apprehended crash-involved drivers had THC concentrations > 1.3 ng/mL. 84 % of the THC-positive drivers tested also positive for alcohol or other drugs. The most frequent combinations were cannabis, sedatives and stimulants. THC > 5 ng/mL was inversely associated with high alcohol or stimulant concentrations. Drivers under 24 years of age tested more often positive for only THC.